Antibody production in mice requires neither vitamin D, nor the vitamin D receptor - Plum, Lori A.; Blaser, William; Peter, Logan; Prahl, Jean; Seeman, Jeremy; DeLuca, Hector F. (Frontiers in Immunology, 2022)
The idea that vitamin D plays a significant role in immunity has been proposed repeatedly for many years. To address this important idea we have carried out studies in mice to determine if vitamin D plays a significant role in antibody production. Two animal models were utilized: mice depleted of vitamin D and mice devoid of the vitamin D receptor. Further, a possible role of hypocalcemia resulting from vitamin D deficiency in antibody production was determined. Neither the absence of vitamin D or the vitamin D receptor nor hypocalcemia affected the ability of mice to mount an antibody response to an antigen challenge. Thus, we found no evidence that vitamin D or normal serum calcium is required for this major form of immunity.